The bundle below: Understanding unconventional oil and gas development through analysis of lease agreements. (May 2016) - Bugden, Dylan; Kay, David; Glynn, Russell; Stedman, Richard
Abstract: Unconventional oil and gas development (UOGD) has recently become the subject of much research. However, neglected during this effort are the leases signed between landowner and industry that act as the foundation for development and may influence the distribution and intensity of associated impacts. These leases amount to an inscribed collection of rules and practices that define a wide variety of conditions related to development. The temporal and geographic distribution of lease terms may directly influence a number of phenomena of interest to scholars studying UOGD. In order to advance research on the subject, we (1) describe and outline research topics that could be addressed by applying social science methods to the analysis of leases and specific lease provisions, (2) discuss challenges and strategies for data collection and (3) review policy implications of lease related research. Highlights: Leases are neglected in research on unconventional oil and gas development (UOGD). Content of lease provisions may shape outcomes and impacts associated with UOGD. Leases are a crucial piece of the larger UOGD policy picture.